Rola administracji rządowej i samorządowej w pozyskiwaniu i wykorzystywaniu środków z Unii Europejskiej - Gorzałczyńska-Koczkodaj, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article presents the different kinds of European Union (EU) funds and programs regarding every governmental and self-governmental administration tiers. The role of municipalities, poviats, voivodships and governmental administration in process of applying for EU funds has also been presented. This role is meant to prepare comprehensive information in the area of possibilities, manners, and EU funds application period, and also preparation of trainings connected with filling out the applications forms and preparation of feasibility studies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 85-92